Legal outsourcing in the shipping industry - Santos, Kayel Clark Ribeiro dos (2019)
The issue that this thesis addresses is the rationale behind the outsourcing decision of legal activities. To address this problem, the purpose of this study has explored what strategy Multinational Enterprises from the Brazilian Shipping Industry apply when deciding to outsource their legal activities. Companies in the industry face a very complex legal environment, in which laws and regulations are fragmented, lack systematization and are often unstable. Therefore, legal outsourcing ought to be a well thought decision, as it has a big impact on companies’ general objectives. The goal of this study then was to uncover the common points that these companies face when making their outsourcing decision. The researcher opted for a qualitative study, more specifically case study, in which data was gathered by conducting interviews with professionals of the industry. Questions were formulated based on both legal management literature and Transaction Cost Theory (TCT). Interviewed professionals had relevant experience with the legal matters that their respective companies face and provided rich answers. Interviews were transcribed and analyzed. Gathered data and discussion of results has demonstrated that indeed legal outsourcing is a well-cared for subject by companies and that the decision to outsource or not relies on many variables, the two most important being volume and complexity. It was also uncovered that contracts and regulatory matters are pressing issues for companies that directly impacts how inside counsel relates to providers. In sum, the results have painted an interesting picture of legal outsourcing in the specific industry, but that might prove to be valuable for future studies and analysis of legal outsourcing in different contexts.